Online prejudice and barriers to digital innovation: Empirical investigations of Chinese consumers. (21st January 2021) - Che, Tong; Peng, Zeyu; Lai, Fujun; Luo, Xin (Robert)
Abstract: China is widely considered a world leader in e‐commerce. In recent years, e‐commerce in China has made significant progress and gone through rounds after rounds of innovations. Technological advancements have enabled the integration of online and offline channels, allowing consumers to choose their preferred shopping channel. Thus, competition and cooperation between online and offline channels have become important issues. Drawing on confirmation bias theory and the unique cultural lens (low uncertainty avoidance and a high level of cynicism) that exists in China, we conceptualize online prejudice and propose a model to analyse how it affects channel selection. A scenario‐based survey, along with an explorative pre‐study, was conducted to test our hypotheses. The results showed that prejudice toward the online channel does exist in China. Further, this online prejudice mediates the relationship between perceived uncertainty and channel selection. That is, uncertainty can induce consumers' online prejudice, which in turn predicts their channel selection behaviour. Furthermore, the mediating effect of online prejudice is contingent upon product type (i.e., experience products vs. search products).